A study of reusability assessment and thermal behaviors for thermoplastic composite materials after melting process: Polypropylene/ thermoplastic polyurethane blends. (10th January 2021) - Lin, Ting An; Lin, Jia-Horng; Bao, Limin
Abstract: In recent years, the excess amount of disposable plastic wastes has gained a concern for the environment. Polypropylene (PP) and thermoplastic polyurethane (TTPU) are both materials that can be properly heated to reform and reuse due to the inherent characteristics of thermoplastic materials. However, the using efficacy may be compromised as the waste may be overheating and thus damaged during the reheating process. Additionally, PP and TTPU are incompatible and immiscible, for which a compatibilizer - polypropylene grafted maleic anhydride (MA) was used. Hence, this study goals to investigate the synergistic effect between these materials and also discuss the compatibilized effect caused by MA. The thermal degradation behavior, melting and crystallization behaviors, and surface morphology of PP/MA/TTPU blends are evaluated under appropriate considerations. In light of the thermal degradation, the presence of thermally stable PP improves the thermal stability of TTPU accordingly. From TGA and DTG results, the addition of MA is also helpful, and therefore the third thermal degradation temperature (T3max ) is increased by 5 °C averagely when compare to neat PP. T1max and T3max of PP/MA/TTPU are postponed about 2 and 4 °C when TTPU content varied from 10 to 30 wt%. SEM images show that the employment of TTPU strengthens the toughness of the surface, and with the aid of 5 wt% MA, PP and TTPU exhibit greater interfacial compatibility and better adhesion. Above all, this study aims to investigate the feasibility of using thermoplastic based on the consideration of how to sustain the excess plastic products and develop the measure to melt-blend diverse thermoplastics for reclamation. The excessive plastics via an easy and convenient melt extrusion process is expected to be regarded as an eco-friendly method for green development on mother earth. Graphical abstract: Image 1 Highlights: Investigate the sustainable reuse probability of thermoplastic materials. Increase the reusability of existed thermoplastic blends via a fast and convenient process. Using an easy and convenient compatibilized method to improve the thermal stability of thermoplastic polyurethane. Solve the phase problem that different plastic cannot be recycled at same time. Discuss the thermal degradation behavior of thermoplastic composite materials after thermal rupture. Thermal degradation behavior of blended thermoplastic materials has been improved. PP improves the thermal behavior of TPU, and TPU solves the low toughness of PP.